Relationship between lactic acid concentration and bacterial spoilage in ground beef. - Nassos, P S (1983)
Lactic acid concentration correlated with organoleptic spoilage of refrigerated, coarsely ground beef stored in casings with low oxygen permeability. The samples were assayed over time for lactic acid concentration, total aerobic plate count, percentage of gram-positive organisms, and pH. Lactic acid increased in all samples, as did the bacterial counts and percentage of gram-positive organisms in the total microflora, the latter representing an increase in the lactic acid-producing bacteria. pH was found to decrease in all samples, with the smallest decrease in pH being observed in the meat sample which maintained the lowest proportion of gram-positive organisms. With samples evaluated by a sensory panel, lactic acid levels were found to correlate inversely with odor acceptability.